An evolutionary conserved zinc finger protein is involved in Toxoplasma gondii mRNA nuclear export. (26th July 2016) - Gissot, Mathieu; Hovasse, Agnès; Chaloin, Laurent; Schaeffer‐Reiss, Christine; Van Dorsselaer, Alain; Tomavo, Stanislas
Summary: Apicomplexan parasites are responsible for some of the most deadly parasitic diseases affecting humans and livestock. There is an urgent need for new medicines that will target apicomplexan‐specific pathways. We characterized a Toxoplasma gondii C2H2 zinc finger protein, named TgZNF2, which is conserved among eukaryotes. We constructed an inducible KO strain (iKO‐TgZNF2) for this gene where the tgznf2 gene expression is repressed in the presence of a tetracycline analog (ATc). We showed that the iKO‐TgZNF2 parasites are unable to proliferate after depletion of the TgZNF2 protein. Complementation with a full length copy of the gene restores the phenotype Moreover, the homolog of this protein in the related apicomplexan Plasmodium falciparum was shown to efficiently rescue the phenotype, suggesting that this pathway is likely conserved among apicomplexan parasites. We demonstrated that the iKO‐mutant lacking TgZNF2 are arrested during the cell cycle during the G1 phase. We identified potential protein partners of this protein among which are spliceosomal complex and mRNA nuclear export components. We confirmed that TgZNF2 is able to bind in vivo to transcripts but splicing is not perturbed in the ATc‐treated parasites. Instead, we demonstrated that TgZNF2 depletion leads to the sequestration of polyA+ mRNAs in the nucleus while ribosomal RNAs are not affected. We discovered a conserved protein with specific apicomplexan functional properties that is essential for the survival of T. gondii . TgZNF2 may be crucial to ensure the correct polyA+ mRNA nuclear export, a function that is conserved in P. falciparum .